Regeneration of irradiation-damaged esophagus by local delivery of mesenchymal stem-cell spheroids encapsulated in a hyaluronic-acid-based hydrogel. (28th January 2021) - Kim, In Gul; Cho, Hana; Shin, Jisoo; Cho, Jung Ho; Cho, Seung-Woo; Chung, Eun-Jae
Abstract : This article presented the efficacy of hyaluronic acid (HA)-gel-encapsulated mesenchymal stem cell spheroids (MSC-SPs) for ultimate treatment of radiation-induced esophageal fibrosis. Abstract : Radiation therapy (RT) is a typical treatment for head and neck cancers. Generally, prolonged irradiation of the esophagus causes esophageal fibrosis due to increased reactive oxygen species and proinflammatory cytokines. This study was designed to determine whether catechol-functionalized hyaluronic acid (HA-CA) hydrogel-encapsulated human mesenchymal stem-cell spheroids (MSC-SPs) could ameliorate damage to the esophagus in a mouse model of radiation-induced esophageal fibrosis. MSC-SPs were cultured in concave microwells 600 μm in diameter at a cell density of 1 × 10 6 cells per mL. Most cells formed spheroids with a 100–300 μm size distribution in concave microwells. MSC-SPs were well maintained in the HA gel, and live–dead staining confirmed that most cells survived. The HA gel containing the MSC-SPs was then injected into the damaged esophageal layer. Inflammatory signs or adverse tissue reactions were not observed after esophageal injection of HA-gel-encapsulated MSC-SPs. Based on Masson's trichrome staining at 4 and 12 weeks postinjection, the inner esophageal layer (IEL) was significantly thinner in the MSC-SP + HA gel group compared to those in the other experimental groups. While the saline and HA gel treatments made the esophageal muscles loose and thick, the MSC-SP + HA gel group showed bundles of tightly packed esophageal muscles, as assayed by desmin immunostaining. qPCR analysis showed that epithelial genes tended to increase over time in the MSC-SP + HA gel group, and the expression of most fibrosis-related genes decreased. This study proposes the potential of using HA-CA-hydrogel-encapsulated MSC-SPs as a promising therapy against radiation-induced esophageal fibrosis.